Primeras secuencias genómicas completas de dos aislamientos Argentinos de rice stripe necrosis virus - Celli, Marcos Giovani; Pinel-Galzi, A.; Filloux, D.; Roumagnac, P.; Hébrard, E. (Asociación Argentina de Fitopatólogos, 2021)
Poster